Students' Accessibility, Attitudes, and Barriers to Using Technologies for Communication and Information - NITIN KUMAR, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2023)
Without a doubt, Information and communication technologies are the main emphasis for how every society is conducted on a daily basis. In the modern world, ICTs make it possible for information to be accessed and exchanged more quickly, easily, and quickly. The study examined the accessibility, mindset, and limitations of final year learners in using computerbased ICTs. With the aid of a carefully constructed questionnaire, data were gathered. Analysis of the data was done using descriptive statistics. This analysis's findings showed that the respondents' median age was 23 years old and that they had various levels of access to seven CBICTs. The interviewees attitudes for utilizing the ICTs were positive and a lack of adequate CBICT resource centers was the main barrier to their adoption. We proposed that, in accordance with the results, a resource center (or centers), if already present, be set up and operational. The presence of a facility centre within the institute should also be extensively publicized so that learners can benefit from the chance to do so and utilize the facilities to the fullest. On the opposite hand, broadband providers should expand their offerings in the region to give a more dependable connection to the internet inside the school because doing so will enable pupils to utilize CB-ICTs inside the school and also for their academic study more successfully.